Innovation, development and sustainability: inspirations of Freeman's economics of hope - Yang, Kejia (Innovation and development, 2022)
This paper introduces Freeman's thoughts on values, economic growth and the environment in the book of The Economics of Hope: essays on technical change, economic growth and the environment. It elaborates how Freeman's ideas and concepts have inspired my doctoral studies which focus on the shift of socio-technical systems towards sustainability. Moreover, it discusses how Freeman's concerns on the role of science, technology and innovation policy for a better society are still inspiring us today.